Futures market of crude palm oil (FCPO) and Kuala Lumpur index (FKLI) as the price discovery in Malaysia / Faqihah Jamak - Jamak, Faqihah (2018)
Price discovery is known as the factors to determine the prices by using demand and supply. This understanding helps investors, fund managers and speculator efficiently to make decisions for asset evaluation. A lot of study states that a future price is one of the main price discovery factors to predict and determine the spot price. However, there were studies regarding futures price as the price discovery is ineffective when the market is efficient. This event happened due to poor regulatory framework and excessive speculation which can cause a moral hazard. Due to this matter, this research attempts to examine whether there is relationship between the future prices towards the spot prices and to identify the main future contract month that affects the spot contract. This study is based on Malaysia derivative product which is crude palm oil (CPO) from the commodity derivative and Kuala Lumpur Composite Index (KLCI) from equity derivative. The entire samples were taken in daily basis from January 2018 until March 2018 from the Bursa Malaysia website. Ordinary Least Squares (OLS) were used as a method for relationship estimation. The findings of this study are positive relationship between future crude palm oil (FCPO) for one-month, two-month and three-month contract prices towards spot crude palm oil and also positive relationship between future KLCI (FKLI) for next-month, next-quarter month and next-two quarter month contract index and spot KLCI.